2018
DOI: 10.1097/ee9.0000000000000026
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal peripartum urinary pyrethroid metabolites are associated with thinner children at 3.5 years in the VHEMBE birth cohort (Limpopo, South Africa)

Abstract: Background: Pyrethroids are the most widely used insecticides globally for domestic, agricultural, and malaria vector control. In 10 countries, dichlorodiphenyl trichloroethane (DDT) is also used for the latter. Thus, high exposure to pyrethroids and DDT have been reported among women and children from rural and/or malaria-endemic areas. Experimental studies suggest that fetal exposure to pyrethroids, particularly cypermethrin, and DDT may have sex-specific growth effects. However, epidemiologic i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
22
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 29 publications
(54 reference statements)
3
22
1
Order By: Relevance
“…No studies of DDT or DDE and allergies have been conducted in countries where DDT is applied for IRS and, to our knowledge, no human study has investigated associations between prenatal exposure to DDT or DDE and non-respiratory allergies. Considering the high levels of exposure to insecticides among populations living in IRS areas (11,12,19,(226)(227)(228)(229)(230)(231)(232)(233) and the potential vulnerability of these populations to the adverse effects of insecticides due to poverty, poor health, and malnutrition (117,(234)(235)(236)(237)(238)(239)(240), the VHEMBE study was developed to determine whether exposure to IRS insecticides was associated with adverse health outcomes among children born and raised in an IRS area. As there is good biological evidence for the effects of DDT and DDE on allergy outcomes but limited research in humans, my study aimed to evaluate whether prenatal exposure to DDT and DDE was associated with elevated odds of allergy symptoms and diagnoses in South African children aged 3.5 years from an area where IRS is conducted annually.…”
Section: Research Objectivesmentioning
confidence: 99%
“…No studies of DDT or DDE and allergies have been conducted in countries where DDT is applied for IRS and, to our knowledge, no human study has investigated associations between prenatal exposure to DDT or DDE and non-respiratory allergies. Considering the high levels of exposure to insecticides among populations living in IRS areas (11,12,19,(226)(227)(228)(229)(230)(231)(232)(233) and the potential vulnerability of these populations to the adverse effects of insecticides due to poverty, poor health, and malnutrition (117,(234)(235)(236)(237)(238)(239)(240), the VHEMBE study was developed to determine whether exposure to IRS insecticides was associated with adverse health outcomes among children born and raised in an IRS area. As there is good biological evidence for the effects of DDT and DDE on allergy outcomes but limited research in humans, my study aimed to evaluate whether prenatal exposure to DDT and DDE was associated with elevated odds of allergy symptoms and diagnoses in South African children aged 3.5 years from an area where IRS is conducted annually.…”
Section: Research Objectivesmentioning
confidence: 99%
“…This practice can result in elevated exposure to dichlorodiphenyltrichloroethane (DDT) and pyrethroids which may interfere with immune function by inducing oxidative stress or by disrupting sex hormones (Pérez-Maldonado et al 2005;Nasuti et al 2007;Han et al 2008;Meeker et al 2009;Yoshinaga et al 2014;Molina et al 2021). Environmental exposure to insecticides from IRS in the Limpopo province of South Africa has recently been associated with accelerated fetal growth (Chevrier et al 2019a), reduced social-emotional scores at 1 and 2 years of age (Eskenazi Brenda et al), allergies in children at 3.5 yrs (Huq et al 2020), hypertensive disorders among pregnant mothers (Murray et al 2018), weight gain in girls (Coker et al 2018), and other health impacts (Bornman et al 2016;Murray et al 2018;Huang et al 2018;Verner et al 2018;Chevrier et al 2019a, b;Huq et al 2020;Eskenazi Brenda et al;Huang Jonathan et al).…”
Section: Introductionmentioning
confidence: 99%
“…Understanding the extent to which these factors contribute to poor health, requires a comprehensive assessment of environmental exposures. The studies that have been conducted to date in sub-Saharan Africa have focused on a limited panel of pesticides or regulated air pollutants (Bornman et al 2016;Murray et al 2018;Huang et al 2018;Verner et al 2018;Chevrier et al 2019a, b;Huq et al 2020;Eskenazi Brenda et al;Huang Jonathan et al). The lack of available technology which can be feasibly deployed with children in a LMIC context has presented challenges in the breadth and scale of environmental measurements that can be captured.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, maternal serum p,p’-DDT concentrations have been positively associated with body weight in girls aged 1−2 years, and maternal urinary pyrethroid metabolite concentrations; notably, cis-3-(2,2-dibromovinyl)-2,2-dimethyl-cyclopropane carboxylic acid (cis-DBCA) and trans-DCCA, have been negatively associated with body weight in boys aged 1−2 years [ 15 ]. Furthermore, an epidemiologic study found that a 10-fold increase in cis-DCCA concentration was associated with a 0.21 kg/m 2 lower body mass index at age 3.5 years [ 16 ]. However, previous studies have not fully examined the relationship between maternal household pesticide exposure during pregnancy and the growth of neonates, whose neurodevelopment is particularly immature.…”
Section: Introductionmentioning
confidence: 99%